B Perencanaan Pembangunan Saluran Irigasi Desa Ngringinrejo Kecamatan Kalitidu - Ferry Setiawan, Mochammad; Mushthofa, Mushthofa; Faqih, Nasyiin (Jurnal Civil Engineering Study, 2023)
Irrigation channels are an important component or system in improving the quality of production in agriculture. Planning for the construction of irrigation canals is needed to serve as a reference or also provide an overview of the work situation, the items to be worked on, the method of implementation, the technical specifications as well, the budget plan according to the working drawings and the stages of the work implementation so that it is in accordance with the standards. The method of implementing the work carried out to achieve the success of the objectives of this activity is through mapping indicators and data elements, field surveys, dashboard designs, focus group discussions. The location for the discussion and trial of the irrigation development planning database was carried out in Ngringinrejo Village, Kalitidu District. The result of this plan is to show that the management of irrigation development planning in the regions has functioned well.